Universidade, diversidade social e diploma de licenciatura: estratégias de rentabilização do título por estudantes de Letras - Roberto Cezar de Souza Silva (2011)
This thesis presents an exploratory study on the strategies used by Language Majors (Licentiates in Portuguese or in Portuguese and English) to increase profitability of their diploma, and the way these strategies relate to certain social properties of the students. Thestudy took into consideration gender, race, religion and place in the sibling position, on top of considering properties such as cultural and economic capital. Analysis of the data collected through a questionnaire answered by a sample of 131 UFMG licentiates observed theprofitability strategies and related them to the social properties. The hypotheses derived from the this analysis were, subsequently, related to six sociological portraits of former Language graduates from the same University who revisited, through interviews, the years they spent inCollege and their transition (or attempts do so) into the job market. Among the main conclusions of the study, the following can be highlighted. (i) Students belonging to the middle classes, in general, were the ones who most invested, mixing long-term professionalinvestments, such as those of academic nature and which might lead to master and doctorate degrees, and short-term investments, such as teaching. (ii) Students with high cultural capital invested predominantly in teaching at language schools, traveling abroad, and in literaturecourses. These last two strategies were the only ones which were also frequently present among the students with more economic capital, and which were shown to take the course more laxly. (iii) Students from the lower classes showed less inclination to invest in relation to the strategies considered in the study. However, a tendency to invest in the linguistics field was observed, which shows a homology between students dispositions and dispositions required by the field. (iv) Social properties such as gender and place in the sibling positionconfirmed in general terms tendencies already observed in literature, which show that women, and the oldest and the youngest children invest more in education. They are, therefore, the ones who most invest in the profitability of their diplomas. It was observed, nevertheless, thatmen and middle siblings showed a tendency to invest in literature courses and, when taken separately, men chose to invest more in teaching. (v) As to color/race, an important finding, and which requires more investigation, was that black students invest heavily in literaturecourses. (vi) Another important finding pertains religion: an inversion of research findings which show that in elementary school there is a connection between academic success and religion since, at this educational level, being religious comes as a positive factor in thestudents academic life. What was seen among religious students in the Language department is that they invest less in strategies than their non-religious counterparts. (vii) Finally, as to what concerns teacher development, it was observed that, in general, students invest muchmore in teaching practices than in courses related to teaching. Hypotheses were drawn so as to explain the aforementioned conclusions. The sociological portraits helped in the formulation and discussion of these hypotheses and showed signs that investing in strategies not always result in good profits. Also, quality and a higher level of reflexivity of the investment point to more beneficial yields. Quality and reflexivity, however, seem to be linked to the structure of the possessed capital, mainly the cultural capital, which the older andthe more incorporated, the more profits seems to yield; and which would point to a tendency to reproduce social inequalities.